STUDI IDENTIFIKASI PENGELOLAAN AIR LIMBAH DOMESTIK KECAMATAN TEMBALANG, CANDISARI, BANYUMANIK DAN PEDURUNGAN KOTA SEMARANG - Nova Henri Rahmawan (Jurnal Teknik Lingkungan, 2013)
Domestic wastewater is one of the complex problems of the city of Semarang, and almost shadowed compared with waste management, is no exception to the District Tembalang, Candisari, Banyumanik and Pedurungan. To identify studies that have been done on the management of domestic waste water in District Tembalang, Candisari, Banyumanik and Pedurungan as the study area.          The method used is the method of qualitative analysis. Data were obtained through interviews using questionnaires and secondary data backed up from the relevant agencies to determine the existing conditions of the study area with the analysis of institutional aspects, public participation, regulatory, financing and operational techniques. Based on the analysis of the obtained data that the domestic waste water management study area was limited to disposal of waste water showers (gray water) in the wastewater drainage and stools (black water) with the processing of septic tanks suspected of using inadequate structures.        Based on the SWOT analysis in policy get domestic wastewater management strategies such as the pursuit of environmentally sound sanitation systems both on-site and off-site, community involvement, and local organizations in the management of domestic waste water, use of technology (decomposing microorganisms) as water treatment plant improvements waste and determining which areas a priority to serve as a pilot area of wastewater management systems are centralized / communal. The area is a priority the implementation of centralized wastewater treatment systems including Sub Sendangmulyo, Meteseh, Bulusan and Housing in Urban Areas Srondol Wetan and Padangsari.